Utilising Natural Science Articles to Improve Critical Thinking in The Digital Era - Fadila Nur Azyza; Rahmi Faradisya Ekapti (Pedagogia: Jurnal Ilmiah Pendidikan, 2025)
In the digital era, critical thinking has become an essential skill for secondary school students, particularly with the emergence of Artificial Intelligence (AI) and the digitalization of science learning that emphasizes media based on scientific articles. This research aims to explore the role of scientific articles in enhancing students' critical thinking skills through the analysis of two articles: slime transformation and the application of Archimedes' principle in hydraulic pumps for car wash machines. Employing a qualitative method with purposive sampling, data were collected through tests and analyzed using Two-Way ANOVA. The results demonstrate that the use of articles about Archimedes' principle in hydraulic pumps for car wash machines and changes in slime helps students connect physics concepts with their application in real-life problem analysis. Articles about slime proved easier to understand due to their concrete nature, whilst hydraulic pump articles required a deep understanding of pressure and buoyancy concepts. The difficulty level of texts significantly influenced students' critical thinking abilities. Integration of scientific literacy in science learning through critical reading activities and discussion can develop students' analytical, evaluative, and inferential skills. This research recommends the scientific article-based literacy approach as an effective strategy for enhancing critical thinking abilities in science education in the digital era.